SOSIALISASI PEMAHAMAN PENDIDIKAN AKUNTANSI PADA SANTRIWATI DI PONDOK PESANTREN AL-KHIKMAH ROWOLAKU PEKALONGAN - Umairo, Tsania; Shofiana, Khuly; Al Rosyadah, Hafidhoh Kholifah; Adinugraha, Hendri Hermawan; Sholihah, Ria Anisatus (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Islamic boarding school is an Islamic religious educational institution that not only teaches religious education but also teaches general education. The development of the world education has changed from year to year along with the challenges in preparing quality human resources who are able to compete in the global era. In the social sciences, accounting is also experiencing development, which initially only focused on matters of a financial nature, now it has begun to penetrate into human behavior. Accounting practice in Indonesia in recent years has experienced very rapid development in various aspects of life, including education. However, the application of accounting in education has not developed rapidly. Unknowingly every human being must carry out accounting practices in their daily lives, although still in a simple way. With the socialization related to the understanding of accounting education, it is hoped that female students can apply accounting knowledge in their daily lives so that female students are able to manage their finances properly and correctly. The method of implementing this activity uses an educational and socialization approach related to accounting education. the majority of female students already know the meaning of accounting and simple examples of applying accounting in everyday life.